2021
DOI: 10.1002/ajhb.23585
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral asymmetry in arm anthropometric measurements according to laterality and nutritional status in children and adolescents from 6 to 12 years old

Abstract: To compare and correlate anthropometric measurements of the left arm versus the right arm and to establish their relation to laterality, sex, and nutritional status in children and adolescents from 6 to 12 years of age. Methods:A cross-sectional study included 605 children and adolescents (285 males; 320 females), with a middle socioeconomic status, that attended an urban elementary school. Anthropometric measurements were taken in both arms, along with height and weight, to assess nutritional status. Self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The results of the mentioned study substantiate the results of our study, in which significant statistical differences were identified between different anthropometric parameters between the right hand (dominant, in the case of the present study) and the left hand. Numerous studies have highlighted anthropometric differences between the right-hand and the lefthand parameters, depending on gender [61][62][63]; ethnicity [64,65]; occupation [66,67]; and laterality [68][69][70]. A study conducted on 161 university student subjects identified significant differences between the male and female samples, with the male group recording an average hand width of 7.57 cm [71].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the mentioned study substantiate the results of our study, in which significant statistical differences were identified between different anthropometric parameters between the right hand (dominant, in the case of the present study) and the left hand. Numerous studies have highlighted anthropometric differences between the right-hand and the lefthand parameters, depending on gender [61][62][63]; ethnicity [64,65]; occupation [66,67]; and laterality [68][69][70]. A study conducted on 161 university student subjects identified significant differences between the male and female samples, with the male group recording an average hand width of 7.57 cm [71].…”
Section: Discussionmentioning
confidence: 99%